Call of the lost ages: a study of the Indus Valley Script - Ganguly, Subhajit (NA Vasto Publishing House, 2013)
The inscriptions found on the various artifacts from the Indus Valley Civilization hold in their hearts hidden chronicles of time. Many unsolved mysteries remain regarding who were these people, how did they suddenly build such an advanced civilization, how were theirs lives like, how much did they interact with their neighbouring cultures, and where did they suddenly vanish . One of the most ancient and advanced civilizations, it mysteriously seems to have disappeared almost suddenly, and that too without any trace. Will the study of the script used by this civilization reveal any clue to these puzzles? Will it help us unravel these ancient mysteries? Finally and most importantly, will a study of the Indus Valley script help us in gaining more knowledge about the ancient world?
Keywords: Civilization-India; Indus Valley Script; Scripts and Inscriptions-Indus Valley Civilization